1988
DOI: 10.1177/0272989x8800800305
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' Diagnoses Compared with Aiaorithmic Differentiation of Causes of Jaundice

Abstract: Clinical data were collected in 194 cases of jaundiced patients treated at the "Adolfo Lopez Mateos" ISSSTE Hospital in Mexico City from July 1985 to July 1986. A copy of the clinical history of each patient was given to each of four physicians--one recently graduated from medical school, another in his first year of gastroenterology, and two others who were experienced gastroenterologists. The same clinical data were processed by a computer set up to use a modified Danish COMIC algorithm. All physicians and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In the first comprehensive review of this research, Meehl () found that actuarial methods equalled or outperformed clinical methods in all 20 instances. His review ignited extensive research comparing the two methods across a range of domains (e.g., Boom et al, ; Dunnette, Kirchner, Erickson, & Banas, ; Goldberg, ). Subsequently, a meta‐analysis by Grove et al () of 136 studies found that 47% favored actuarial predictions, 48% yielded equal performance, and only 6% favored clinical predictions.…”
mentioning
confidence: 99%
“…In the first comprehensive review of this research, Meehl () found that actuarial methods equalled or outperformed clinical methods in all 20 instances. His review ignited extensive research comparing the two methods across a range of domains (e.g., Boom et al, ; Dunnette, Kirchner, Erickson, & Banas, ; Goldberg, ). Subsequently, a meta‐analysis by Grove et al () of 136 studies found that 47% favored actuarial predictions, 48% yielded equal performance, and only 6% favored clinical predictions.…”
mentioning
confidence: 99%
“…This Danish team used two other methods in the same population with the same data: a logistic discrimination model (24) and a decision tree (23). The logistic discrimination model with minor changes was proved robust in Sweden (19) and in Mexico (12); it was superior t o clinicians in Mexico (13) but not in Denmark (22). The three methods have been compared: the Bayes rule is the most accurate biologic data for the diagnosis of 11 possible causes of jaundice in 309 subjects.…”
Section: Review Of Publicationsmentioning
confidence: 99%